Two-dimensional model for subthreshold current and subthreshold swing of graded-channel dual-material double-gate (GCDMDG) MOSFETs. (June 2017) - Goel, Ekta; Kumar, Sanjay; Singh, Balraj; Singh, Kunal; Jit, Satyabrata
Abstract: The subthreshold performance of graded-channel dual-material double-gate (GCDMDG) MOSFETs is examined through two-dimensional (2D) analytical modeling of subthreshold-current (SC) and subthreshold-swing (SS). The potential function obtained by using the parabolic approach to solve the 2D Poisson's equation, has been used to formulate SC and SS characteristics of the device. The variations of SS against different device parameters have been obtained with the help of effective conduction path parameter. The SC and SS characteristics of the GCDMDG MOS transistor have been compared with those of the dual-material double-gate (DMDG) and simple graded-channel double-gate (GCDG) MOS structures to show its better subthreshold characteristics over the latter two devices. The results of the developed model are well-agreed with the commercially available SILVACO ATLAS™ simulator data.